2013
DOI: 10.1073/pnas.1301652110
|View full text |Cite
|
Sign up to set email alerts
|

Development of cortical microstructure in the preterm human brain

Abstract: Cortical maturation was studied in 65 infants between 27 and 46 wk postconception using structural and diffusion magnetic resonance imaging. Alterations in neural structure and complexity were inferred from changes in mean diffusivity and fractional anisotropy, analyzed by sampling regions of interest and also by a unique whole-cortex mapping approach. Mean diffusivity was higher in gyri than sulci and in frontal compared with occipital lobes, decreasing consistently throughout the study period. Fractional ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
289
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 308 publications
(324 citation statements)
references
References 47 publications
(42 reference statements)
30
289
1
Order By: Relevance
“…Notably, this pattern was independent of preceding clinical‐image relationships and also total ICV. This multimodal imaging marker was striking in the relative sparing of primary cortex, which may reflect the relative maturity of primary cortex at this age,8 and in the changes in diffusivity in the lentiform nuclei, which may reflect altered cell density. Animal models of preterm birth have shown that prolonged respiratory ventilation is associated with adverse cerebral outcomes, including tissue volume loss and white matter injury,46 and we have previously demonstrated global volume losses and alterations to white matter microstructure in infants with chronic lung disease 35, 47.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, this pattern was independent of preceding clinical‐image relationships and also total ICV. This multimodal imaging marker was striking in the relative sparing of primary cortex, which may reflect the relative maturity of primary cortex at this age,8 and in the changes in diffusivity in the lentiform nuclei, which may reflect altered cell density. Animal models of preterm birth have shown that prolonged respiratory ventilation is associated with adverse cerebral outcomes, including tissue volume loss and white matter injury,46 and we have previously demonstrated global volume losses and alterations to white matter microstructure in infants with chronic lung disease 35, 47.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous works have been published in the literature that have improved our understanding of the perinatal brain (Ball et al, 2013b(Ball et al, , 2017Counsell et al, 2013;Doria et al, 2010;Kapellou et al, 2006;Keunen et al, 2017;Krishnan et al, 2017;Xue et al, 2007;Dubois et al, 2008a,b;Pienaar et al, 2008;RodriguezCarranza et al, 2008;Awate et al, 2010;Hill et al, 2010;Rathbone et al, 2011;Moeskops et al, 2013;Li et al, 2014b,a;Meng et al, 2014;Nie et al, 2014;Wang et al, 2014;Engelhardt et al, 2015;Lefevre et al, 2015;Li et al, 2015b;Moeskops et al, 2015;Li et al, 2016;Hazlett et al, 2017). Study- ing the developing connectome will open up many opportunities in future, not least because neonatal brain imaging data is changing rapidly, at scales that can be clearly resolved using current MRI technology.…”
Section: Discussionmentioning
confidence: 99%
“…During this time, the cellular foundations of our advanced cognitive abilities are mapped out, as connections start to form between distant regions (Ball et al, 2013b;Van Essen, 1997), myelinating, and later pruning, at different rates. Alongside the development of this neural infrastructure, functional brain activations start to be resolved (Doria et al, 2010), reflecting the development of cognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This anatomical distribution of areas affected by prematurity may reflect known developmental programming: microstructural maturation of primary sensory cortex seems to occur earlier than heteromodal cortex (37), and growth association protein, which is present in growing axons but lost when stable connections are made (47), is absent from axonal connections to first-order relays (44) but persists in regions of heteromodal cortex, where it may mediate experience-dependent plasticity (48). Cortical areas receiving inputs from first-order thalamic relays also mature earliest with regards to myelin formation and cortical thickness (49), whereas thalamocortical units found in this study to be affected by prematurity involve cortex which takes the longest to reach peak cortical thickness (50).…”
Section: Discussionmentioning
confidence: 99%